2012
DOI: 10.1111/j.1463-1318.2012.02976.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on recurrence and severity of left colonic diverticulitis

Abstract: AD does not present a more aggressive clinical course in younger patients and it can be safely managed using the same strategy as in middle aged and older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 28 publications
2
30
2
8
Order By: Relevance
“…Indeed, we found that young patients have an increased risk of recurrence compared with older adults. 4,5,40,48,50,51,53 Again, this…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Indeed, we found that young patients have an increased risk of recurrence compared with older adults. 4,5,40,48,50,51,53 Again, this…”
Section: Discussionmentioning
confidence: 88%
“…Only three studies assessed re-recurrent disease and were limited to episodes associated with a hospital admission. 5,51,53 We know surprisingly little about this population, the natural history of their illness, and their burden of disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No obstante, al año siguiente se publica un estudio en el que analizan 686 pacientes dividiéndolos en 3 grupos según la edad ( < 45 años, entre 45 y 70 años y >70), demostrando que el curso de la diverticulitis no es más agresivo en los pacientes más jóvenes 35 . Así lo confirma también un estudio de Ritz et al 36 .…”
Section: -Discusiónunclassified